Beyond the Shore: Reconstructing Islamic Worship Jurisprudence for Fishing Communities Through the Lens of Fiqh Sosial - Sahal Mahfudh; Mohammed Adam Mohammed Abdulali (Santri: Journal of Pesantren and Fiqh Sosial, 2026)
Fishing communities in Pati, Central Java, demonstrate strong Islamic devotion but encounter a persistent "formalistic deadlock" when classical Shafi’i rulings on worship are strictly applied to the challenging and variable conditions of months-long deep-sea voyages. Existing scholarship has only partially addressed this issue, relying either on rigid textual (qaulī) prescriptions or on descriptive sociological analysis. This article aims to reconstruct an integrated worship jurisprudence (fiqh al-baḥr) for these communities, extending the scope of ubudiyyah beyond purification and prayer to include fasting (sawm), almsgiving (zakāt), and the customary maritime ritual Sedekah Laut. The study adopts a qualitative, library-based juridical methodology, employing a manhajī (methodological) approach aligned with K.H. Sahal Mahfudh’s Fiqh Sosial, prioritising maqāṣid al-sharīʿah—particularly the preservation of life (ḥifẓ al-nafs) and property (ḥifẓ al-māl)—and reading classical texts (turāth) in dialogue with ten recent scholarly works (2020–2026) and empirical data from the Pati coastal context. The results yield a four-pillar Fiqh Nelayan: (1) GPS navigation as an obligatory means (wasīlat al-wājib) for qibla determination, supported by onboard water filtration as istiḥālah; (2) rukhṣah from fasting during extended voyages with compensatory qaḍāʾ; (3) productive zakāt from maritime yields to dismantle structural poverty; and (4) the transformation of Sedekah Laut into an Eco- Sharīʿah conservation covenant. This reconstruction positions Islamic law as an emancipatory social ethic, empowering coastal communities with dignity and ecological sustainability.